Split Application under Reduced Nitrogen Rate Favors High Yield by Altering Endogenous Hormones and C/N Ratio in Sweet Potato - Xiangbei Du; Xinyue Zhang; Lingcong Kong; Min Xi (Agronomy, 2020)
A process for reducing the nitrogen (N) application rate while maintaining sweet potato yield urgently needs to be determined. A two-year pot experiment was conducted with three N management strategies to explore the mechanism underlying yield increase caused by a split application under a reduced N rate through an investigation of the changes in the carbon (C)-N metabolism and endogenous hormone. Results revealed that, compared with conventional basal N management, split application under a reduced N rate increased storage root yield by 22.1% through improving the storage root number and mean storage root weight by 12.3% and 10.2%, respectively. During the storage root formation period, split application under a reduced N rate decreased the soil-available N (AV-N) content and N content in storage root, inducing elevated C content, C/N ratio, auxin (IAA) content, zeatin and zeatin riboside (Z + ZR) content and reduced abscisic acid (ABA) content in storage roots, promoting storage root formation. During the storage root bulking period, split application under a reduced N rate appropriately elevated the soil AV-N content and N content in the storage root which, together with increased ABA content, which enhanced C content and C/N ratio in the storage root, resulted in an improved mean storage root weight. These results will facilitate the generation of appropriate N management strategies to improve sweet potato productivity.